Evaluation of Cholinesterase Activities During in Vivo Intoxication Using an Electrochemical Sensor Strip – Correlation With Intoxication Symptoms - Jana Zdarova-Karasova (Sensors, 2009)
Cholinesterase activity in blood of laboratory rats was monitored. Rats were intoxicated with paraoxon at dosis of 0 – 65 – 125 – 170 – 250 – 500 nmol. The 250 nmol dose was found to be the LD50. An electrochemical sensor was found useful to provide information about cholinesterase activity. The decrease of cholinesterase activity was correlated to intoxication symptoms and mortality level. It was found that the symptoms of intoxication are not observed while at least 50% of cholinesterase activity in blood remains. The minimal cholinesterase activity essential to survival is around 10%, when compared with the initial state. No changes in levels of low moleculary weight antioxidants were observed.